Considerations and recommendations for selection and utilization of upper extremity clinical outcome assessments in human spinal cord injury trials. Issue 5 (May 2018) - Jones, Linda; Bryden, Anne; Wheeler, Tracey; Tansey, Keith; Anderson, Kim; Beattie, Michael; Blight, Andrew; Curt, Armin; Field-Fote, Edelle; Guest, James; Hseih, Jane; Jakeman, Lyn; et al.
Abstract Study design This is a focused review article. Objectives This review presents important features of clinical outcomes assessments (COAs) in human spinal cord injury research. Considerations for COAs by trial phase and International Classification of Functioning, Disability and Health are presented as well as strengths and recommendations for upper extremity COAs for research. Clinical trial tools and designs to address recruitment challenges are identified. Methods The methods include a summary of topics discussed during a two-day workshop, conceptual discussion of upper extremity COAs and additional focused literature review. Results COAs must be appropriate to trial phase and particularly in mid-late-phase trials, should reflect recovery vs. compensation, as well as being clinically meaningful. The impact and extent of upper vs. lower motoneuron disease should be considered, as this may affect how an individual may respond to a given therapeutic. For trials with broad inclusion criteria, the content of COAs should cover all severities and levels of SCI. Specific measures to assess upper extremity function as well as more comprehensive COAs are under development. In addition to appropriate use of COAs, methods to increase recruitment, such as adaptive trial designs and prognostic modeling to prospectively stratify heterogeneous populations into appropriate cohorts should be considered. Conclusions With an increasing number of clinical trials focusing on improving upper extremity function, it is essential to consider a range of factors when choosing a COA. Sponsors Craig H. Neilsen Foundation, Spinal Cord Outcomes Partnership Endeavor.